Analisis Pemasaran Konten Media Sosial pada Perum Bulog Wilayah DKI Jakarta - Banten: Instagram @bulogbisnis.jakarta - Clara Elena; Sholikhah Sholikhah; Dewi Agustin Pratama Sari (Jurnal Manajemen Bisnis Era Digital, 2024)
The purpose of this research is to analyze social media content marketing. This research uses a descriptive method with a qualitative approach. The subject of this research is Instagram @bulogbisnis.jakarta. The method in this research is a case study. The data sources in this study are primary sources. Data analysis in this study uses thematic analysis. The theory used in this research is using Chris Heurer 4C theory (Context, Communication, Collaboration, Connection) The activities used in data analysis are data reduction, data presentation, and conclusion drawing. Based on the results of research processing and analysis, the following conclusions were drawn: The conclusion can be gained at the context point, namely the content uploaded by Instagram @bulogbisnis.jakarta is easy to understand in terms of meaning and communicative language style. The conclusion that was gained at the communication point was that the content uploaded by Instagram @bulogbisnis.jakarta was quite clear and accurate with the actual situation but received few comments due to the lack of creativity in the content, on the other hand the uploaded content still created a positive perception of Bulog's image and made a big contribution because it created new orders through direct messages and call centers listed in the uploaded content. The conclusion that can be gained at the collaboration point is that Instagram @bulogbisnis.jakarta has utilized the features available on Instagram to make it easier for followers to see the uploaded content and Bulog has collaborated quite well with Instagram @bulogbisnis.jakarta by reposting uploads from Instagram @bulogbisnis.jakarta. The conclusion gained at the connection point is that it has made improvements in the speed of response both from comments, direct messages and call centers and to maintain good and sustainable relationships with followers, Instagram @bulogbisnis.jakarta provides appreciation through giveaway content.